Flame-Retardant Polyamide 6/Carbon Nanotube Nanofibers: Processing and Characterization. Issue 3 (September 2015) - Yin, Xiaoli; Krifa, Mourad; Koo, Joseph H.
Polyamide 6 (PA6) was melt-blended with an intumescent flame retardant (FR), multi-wall carbon nanotubes (MWNTs), and nanoclay particles to produce multi-component FR-PA6 nanocomposites. FR-PA6 nanofibers were processed from varied nanocomposite formulations via electrospinning. Electrospinnability, morphology, along with combustion and thermal properties of the nanofibers were investigated. Both the bulk-form nanocomposites and the electrospun nanofiber membranes exhibited significantly improved combustion properties, including both Heat Release Rate and Total Heat Release. On the other hand, thermal stability appeared compromised. With proper FR additive concentrations, synergism between MWNTs and nanoclay was observed.